Child health after preimplantation genetic testing. Issue 3 (March 2021) - Lewis, Sharon; Amor, David J; Glynn, Anne; Wilton, Leeanda; Halliday, Jane
Abstract: Research question: Despite the increasing use of preimplantation genetic testing (PGT) for aneuploidy and monogenic diseases, for children conceived using PGT there is limited follow-up beyond 2 years of age. This study examined the health, well-being and development of school-aged children (5–8 years old) conceived following PGT. Design: Retrospective cohort study of children conceived after IVF with PGT (exposed cohort) and children conceived after IVF without PGT (unexposed cohort) at two IVF clinics in Melbourne, born between 2000 and 2008, recruited with a 1:2 ratio. Mothers of the children completed a questionnaire asking child-specific questions regarding health and well-being, mental health, development, educational achievement and family-specific questions regarding family functioning and parent–child attachment. Results: A total of 155 participants were recruited to the PGT cohort and 303 participants to the IVF-only cohort. There were no differences between the two cohorts with regards to maternal characteristics, birth defect frequency and pregnancy characteristics, apart from delivery by Caesarean section, which was more frequent in PGT singletons (55%) compared with IVF-only singletons (36%). While no significant differences between the PGT and IVF-only cohorts were found for the majority of general health and psychological scales, there were differences when compared with population data. Children in the exposed cohort appeared to have more positive outcomes in many of the measures. Conclusion: The data from this study suggest that PGT does not cause adverse outcomes in children. However, the nature (self-report) and small sample size of the study must be taken into consideration when interpreting the data.